ØªØÙ„ÙŠÙ„ Ø§Ù„ØªÙ†ÙÙŠØ° Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„Ù…ØØ§Ø¯Ø«Ø© ÙÙŠ ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© - Hidayatul Musaadah; Siti Khoirun Nihaya; Zakiyah Isnawati (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
This article explains the importance of applying Arabic learning methods. In the learning process there are several methods of understanding the skill that must be mastered in learning. one of them is the muhasatsah method. In this article the reader is invited by the writer to the author to discuss various matters related to Muhadatsah method in learning Arabic. Including characteristics, benefits, principles, basic concepts, and language skill and objective. With us learning the method of muhadatsah in language learning, it is expected that we can do learning Arabic with the maximum and can motive students to be more happy and easy to learn Arabic.